Successes and challenges of learning to support children post-COVID-19 - Megan Adams; Sanjuana Rodriguez; Karla Ramirez; Allison Garefino; Virginie Jackson (Journal of College Orientation, Transition, and Retention)
This study investigated the experiences of faculty mentors and college students majoring in education or social work during a four-week summer program serving children in first and second grade. The college students worked as tutors, implementing an evidence-based reading program supported by training in mental health and behavior interventions. The case study design was used to determine impacts on the college students. Observations of college students, reflections from the college students, and vignettes from the faculty mentors were the data sources for the study. The key themes resulting are challenges working with children from socioeconomically and linguistically marginalized communities; successes and rewards of working with children; confidence as teachers; and mental health. The research indicates that further study is needed on embedding social work tenets into education programs on college campuses and mental health services are needed for all students K-20 post-COVID.